Do they return for food? Exploring the role of memorable food experiences and destination image - Eviana, Nova; Yusrini, Lenny (Turyzm/Tourism, 2025)
The study investigates the intricate relationships among local food experiences, memorable tourism experience, destination image and tourists’ revisit intentions. The research employed a quantitative research design. Data collection was conducted between January and March 2024 and analysed with structural equation modelling. Results indicate that while local food may not directly impact revisit intentions, it significantly shapes memorable tourism experiences and destination image. Memorable experiences, in turn, strongly predict revisit intentions. Local food serves a crucial role in enhancing destination image, contributing to overall attractiveness. However, the direct influence of destination image on revisit intentions could have been more conclusive, warranting further investigation into mediating factors and contextual influences. The study emphasizes the importance of integrating local food into destination branding and management strategies to enhance tourists’ perceptions and increase revisit intentions. Future research should explore additional factors influencing revisit intentions and clarify the complex relationships between local food, memorable experiences, destination image and tourist behaviour.